The role of the project manager’s communication soft skills on risk management practices in Libyan oil & gas projects: The moderating role of experience - Elkbuli, Mohamed O.; Zulkiple, A.; Lee, Chia Kuang (American Institute of Physics Inc., 2023)
The project management community is actively debating how to identify the factors that lead to project success. The project manager’s position and its impact on the project’s overall outcomes have become a hot topic among researchers, practitioners, and academics. The attempts to define the traits and competencies of good project managers have led to the recognition that a range of competencies other than those simply technical is required. Because a project manager’s human and leadership skills are critical to the project’s success, these abilities must be taught and developed as part of project management education. In response to this demand, this study aims to identify factors affecting soft managerial skills in Libya’s oil and gas projects and a methodology for implementing risk management principles in oil and gas projects to improve their efficiency. Using SmartPLS 3 and structural equation modelling (SEM), the paper attempted to conserve, characterize, and analyze evidence for this study. As a result, this study recommends how managerial soft skills may improve continuous risk management procedures and intra-project communication in Libya’s oil and gas sector. This system will assist project stakeholders in the planning phase and aid in producing high-quality projects that are closely monitored in terms of time and cost.